S115 The effects of hypoxia on neutrophil-mediated tissue damage in the lung. (14th November 2013) - Hoenderdos, K; Hirst, RA; Porter, L; Chen, C; Lodge, K; O'Callaghan, C; Chilvers, ER; Condliffe, AM
Abstract : Sites of infection and inflammation are profoundly hypoxic, requiring neutrophils to function under low oxygen tensions. Although neutrophils are well adapted and can rely on glycolytic metabolism, hypoxia still impairs the neutrophil oxidative burst, reduces bacterial killing and delays apoptosis. 1 As neutrophil proteases have been implicated in lung diseases such as COPD, we hypothesised that hypoxia might also promote neutrophil degranulation, with an enhanced potential for neutrophil-mediated tissue injury. Neutrophils isolated from healthy volunteers were subjected to normoxia (20 kPa) or hypoxia (3 kPa) and subsequently activated with GM-CSF (10 ng/ml) and the bacterial tri-peptide fMLP (100 nM). A549 cells and ciliated human primary bronchial epithelial (NHBE) cells were exposed to neutrophil supernatants, the extent of cellular damage was determined by MTT assay (A549 cells), EM ultrastructure and cleaved caspase 3 staining. Ciliary function was also investigated using video microscopy in the ciliated NHBE cells. Hypoxic incubation for 4 hours resulted in a 3–5 fold increase in neutrophil degranulation; this was evident for active elastase, MPO, MMP-9 and lactoferrin and hence occurred from all granule sub-types. Supernatants from hypoxic neutrophils induced 50% more cell death in A549 cells compared to supernatants from normoxic neutrophils. NHBE cells exposed to supernatants from hypoxic versus normoxic neutrophils suffered more cellular damage (EM; images were scored for cytoplasmic blebbing, vacuole formation and dead cells), an increase in LDH activity (from 35.7 ± 6 to 50.2 ± 0.7 nmol/min/ml, was indicative of cell death), increased cleaved caspase 3 staining was shown to be an indicator of apoptosis and there was a substantial increase in the proportion of dyskinetic and immotile cilia. In conclusion; hypoxia induced a destructive neutrophil phenotype with delayed apoptosis, impaired bacterial killing and increased release of histo-cytotoxic proteases. This phenotype may be important for understanding the mechanisms of chronic inflammatory diseases like COPD. Funded by the British Lung Foundation and NIHR Cambridge BRC. References: McGovern, N. N. et al . Hypoxia selectively inhibits respiratory burst activity and killing of Staphylococcus aureus in human neutrophils. J. Immunol. Baltim. Md 1950 186, 453–463 (2011).